2020
DOI: 10.15252/embr.202050410
|View full text |Cite
|
Sign up to set email alerts
|

Non‐recombinogenic roles for Rad52 in translesion synthesis during DNA damage tolerance

Abstract: DNA damage tolerance relies on homologous recombination (HR) and translesion synthesis (TLS) mechanisms to fill in the ssDNA gaps generated during passing of the replication fork over DNA lesions in the template. Whereas TLS requires specialized polymerases able to incorporate a dNTP opposite the lesion and is error-prone, HR uses the sister chromatid and is mostly error-free. We report that the HR protein Rad52-but not Rad51 and Rad57acts in concert with the TLS machinery (Rad6/Rad18-mediated PCNA ubiquitylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 74 publications
(158 reference statements)
1
38
0
Order By: Relevance
“…One possibility is that these physical interactions provide a platform for the landing of replication and repair factors at the proximity of stressed forks. Recently, we showed that Rad51 and Rad52 have a non-recombinogenic role in TLS by facilitating the recruitment of the Rad6/Rad18 complex to chromatin (Cano-Linares et al, 2021). Proliferating cell nuclear antigen (PCNA) ubiquitylation by Rad6/Rad18 is necessary for the recruitment of TLS polymerases (Bienko et al, 2005) and facilitates replication fork advance in the presence of a damaged template (Ortiz-Bazá n et al, 2014).…”
Section: Accessmentioning
confidence: 99%
See 2 more Smart Citations
“…One possibility is that these physical interactions provide a platform for the landing of replication and repair factors at the proximity of stressed forks. Recently, we showed that Rad51 and Rad52 have a non-recombinogenic role in TLS by facilitating the recruitment of the Rad6/Rad18 complex to chromatin (Cano-Linares et al, 2021). Proliferating cell nuclear antigen (PCNA) ubiquitylation by Rad6/Rad18 is necessary for the recruitment of TLS polymerases (Bienko et al, 2005) and facilitates replication fork advance in the presence of a damaged template (Ortiz-Bazá n et al, 2014).…”
Section: Accessmentioning
confidence: 99%
“…Tagged and deletion strains were constructed by a PCR-based strategy (Longtine et al, 1998). The uSCE system was backcrossed five times into the W303 background (Cano-Linares et al, 2021). The integrative plasmids pRS551-L120A,V181A (a gift from N. Hollingsworth) and pRS306-r51.54 (see Method details) were used to replace CDC7 and RAD51 with cdc7-as3 (W303cdc7as3-2) and rad51m (w303.51.54-7), respectively.…”
Section: Declaration Of Interestsmentioning
confidence: 99%
See 1 more Smart Citation
“…The DNA repair mechanism of tumor cells is a key factor affecting cell chemosensitivity. Recently, studies have shown that translesion DNA synthesis (TLS) is an emergency repair mechanism in eukaryotic cells [8][9][10]. Translesion DNA synthesis plays an important role in the repair of DNA damage induced by ionizing radiation, and therefore enhances the radiation resistance of tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…Translesion DNA synthesis plays an important role in the repair of DNA damage induced by ionizing radiation, and therefore enhances the radiation resistance of tumor cells. DNA polymerase ζ (pol ζ) is the key component of TLS [9][10][11][12]. It mainly consists of two subunits, REV3L and REV7.…”
Section: Introductionmentioning
confidence: 99%